2007
DOI: 10.1073/pnas.0707203104
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenomic analysis of the emergence of GC-rich transcription elements

Abstract: We have applied a comparative phylogenomic analysis to study the evolutionary relationships between GC content, CpG-dinucleotide content (CpGs), potential nuclear factor I (NFI) binding sites, and potential Z-DNA forming regions (ZDRs) as representative structural and functional GC-rich genomic elements. Our analysis indicates that CpG and NFI sites emerged with a general accretion of GC-rich sequences downstream of the eukaryotic transcription start site (TSS). Two distinct classes of ZDRs are observed at dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 26 publications
(34 reference statements)
1
40
2
Order By: Relevance
“…SIBZ analysis has found an enrichment of regions with Z-forming potential around transcription start sites (TSSs) [31]. Other less rigorous methods, such as Z-Catcher and Z-Hunt , have found qualitatively similar patterns of Z-DNA enrichment around TSSs [31], [55], [69], [70], although they find different numbers of sites than we do. Here we examine how superhelical B-Z transitions compete with denaturation at these locations, as well as in the regions where transcription terminates.…”
Section: Resultsmentioning
confidence: 41%
See 1 more Smart Citation
“…SIBZ analysis has found an enrichment of regions with Z-forming potential around transcription start sites (TSSs) [31]. Other less rigorous methods, such as Z-Catcher and Z-Hunt , have found qualitatively similar patterns of Z-DNA enrichment around TSSs [31], [55], [69], [70], although they find different numbers of sites than we do. Here we examine how superhelical B-Z transitions compete with denaturation at these locations, as well as in the regions where transcription terminates.…”
Section: Resultsmentioning
confidence: 41%
“…There has been previous evidence of depletion of Z-form DNA around TSS of prokaryotic genomes [69], [73]. Here we investigate these properties together by using the BDZ trans algorithm to analyze the average transition behavior of 4456 E. coli gene sequences.…”
Section: Resultsmentioning
confidence: 99%
“…The GT:AC repeats are estimated to account for more than 0.25% of the entire human genome [35]. A computer-based thermodynamic search strategy (Z-Hunt-II) used by the Ho group to analyze the complete human genome showed that Z-DNA-forming sequences occur approximately once every 3,000 bp [70]. Furthermore, Z-DNA-forming regions were found to be distinctly located near the 5’ ends of genes in the genome, and the proximity between these regions and the transcription start sites became more pronounced during the divergence from prokaryotes to eukaryotes [70].…”
Section: Genome-wide Analyses and Evolutionary Relationshipsmentioning
confidence: 99%
“…A computer-based thermodynamic search strategy (Z-Hunt-II) used by the Ho group to analyze the complete human genome showed that Z-DNA-forming sequences occur approximately once every 3,000 bp [70]. Furthermore, Z-DNA-forming regions were found to be distinctly located near the 5’ ends of genes in the genome, and the proximity between these regions and the transcription start sites became more pronounced during the divergence from prokaryotes to eukaryotes [70]. Therefore, the location bias of these GT:AC repeats is supportive of Z-DNA formation and stabilization by the transient surges in negative supercoiling associated with transcription.…”
Section: Genome-wide Analyses and Evolutionary Relationshipsmentioning
confidence: 99%
“…The authors suggested that Z-DNA upstream of the nuclear factor-1 binding site helped to maintain the gene in its activated, nucleosome-free state (nucleosomes do not bind to the very rigid Z-DNA form (Ausio et al, 1987)). In support of its potential role in the regulation of eukaryotic genes, we have found that Z-forming sequences accumulate near the transcription start site of genes in humans and other eukaryotes (Khuu et al, 2007;Schroth et al, 1992), and that ~80% of the genes in human chromosome 22 have at least one Z-DNA sequence in the vicinity of their transcription start sites (Champ et al, 2004). The discovery of protein domains having very high specificity for Z-DNA (Rich and Zhang, 2003), in some cases with nanomolar K D 's, have suggested additional functions that include, for example, RNA editing and gene transactivation.…”
Section: Z-dnamentioning
confidence: 99%